EXPERIMENTAL CONSTRAINTS ON THE HYDROTHERMAL REACTIVITY OF ORGANIC ACIDS AND ACID ANIONS: I. FORMIC ACID AND FORMATE - McCollom T.M.; Seewald J.S. (My University, 2003)
A series of hydrothermal experiments covering a range of temperatures from 175 to 260°C examined the decomposition of formic acid and formate and also investigated the production of formate from reduction of CO2. Decomposition rates measured in this study, which were conducted in gold-TiO2 reactors, were several orders of magnitude slower than those reported in previous studies conducted in steel and Ti-metal reactors, indicating the previous studies substantially overestimated the rate of the reaction owing to reactor catalysis. Although experiments were conducted with several different minerals present (hematite, magnetite, serpentinized olivine, NiFe-alloy), the decomposition rates were similar in each experiment once the effects of fluid pH were accounted for, suggesting that the minerals had no effect on the stability of formic acid or formate. At higher temperatures (>225°C), the rates of both the decomposition of formate and the reduction of CO2 to formate were sufficiently rapid that reactions between dissolved CO2 and formate rapidly attained a state of metastable thermodynamic equilibrium. The results suggest that the amount of formate in many subsurface and hydrothermal fluids is likely to be controlled by equilibrium with dissolved CO2 at the prevailing oxidation state and pH of the fluid. This may account for the high concentrations of formate observed in strongly reducing environments such as serpentinites, as well as the low concentrations relative to other organic acid anions in mildly reducing environments such as oil-filed brines and formation waters in sedimentary basins. Although formate has been suggested to be a reaction intermediate in the formation of abiotic hydrocarbons from reduction of aqueous CO2, production of hydrocarbons was not observed in any of the experiments, except for trace amounts of methane, despite high concentrations of formate and strongly reducing conditions.